Tailgut Cyst—Gynecologist’s Pitfall: Literature Review and Case Report - Andrei Mihai Malutan; Viorela-Elena Suciu; Florin Laurentiu Ignat; Doru Diculescu; Razvan Ciortea; Emil-Claudiu Boțan; Carmen Elena Bucuri; Maria Patricia Roman; Ionel Nati; Cristina Ormindean; Dan Mihu (Diagnostics)
Background and Clinical Significance: Retrorectal cystic hamartomas (“Tailgut cysts”) are rare developmental cysts that appear in the retrorectal space, arising from aberrant remnants of the post-anal primitive gut in case of an incomplete embryogenetic involution. Case Presentation: We present the case of a 30-year-old woman with a history of chronic lower abdominal pain. Other digestive symptoms, like rectal fullness, constipation, pain on defecation, rectal bleeding or genitourinary obstruction symptoms, were not associated. During a period of 3 years, she underwent several surgical procedures for ovarian cysts, without relieving the symptomatology. A computed tomography (CT) scan showed a presacral tumor with a right pararectal development. A surgical resection of the lesion using an anterior approach was performed, with the final pathological diagnosis of a retrorectal cystic hamartoma (“tailgut cyst”). Conclusions: This case underlines the fact that retrorectal masses can be challenging to diagnose, and tailgut cysts must be taken into consideration in cases of perirectal tumors in patients with a history of multiple failed procedures and surgeries.